Предмет: Алгебра, автор: vatrushozi123

только второй пример

Приложения:

Ответы

Автор ответа: Danil12584
1

( {a}^{2}  +  {b}^{2} )( {a}^{4}  -  {a}^{2}  {b}^{2}  +  {b}^{4} ) + ( {a}^{3}  -  {b}^{3} )( {a}^{3}  +  {b}^{3} ) = 2 {a}^{6}  \\  {a}^{6}  +  {b}^{6}  + ( {a}^{3}  -  {b}^{3} )( {a}^{3}  +  {b}^{3} ) = 2 {a}^{6}  \\  {a}^{6}  +  {b}^{6}  +  {a}^{6}  -  {b}^{6}  = 2 {a}^{6}  \\  {a}^{6}  +  {a}^{6}  = 2 {a}^{6}  \\ 2 {a}^{6}  = 2 {a}^{6}
Похожие вопросы
Предмет: Алгебра, автор: maxim472
Предмет: Физкультура и спорт, автор: anna070309